Does workplace ostracismce lead to counterproductive work behavior in healthcare employees: the role of transactional and relational psychological contract breach - Muhammad Rizwan Sabir; Muhammad Bilal Majid; Muhammad Zia Aslam; Abdul Rehman; Sumaira Rehman (Cogent Business & Management, 2024)
AbstractWith the presence of negative organizational behaviors, not only is the employee’s productivity and job satisfaction affected, but the entire organizational performance of employees also declines. Workplace ostracism affects employees’ psychological well-being by fostering exhaustion of their emotional, psychological, and material resources, significantly influencing counterproductive work behavior. The present research also addresses the emerging negative workplace behaviors by studying the mediation of transactional and relational psychological contract breaches. The research has adopted a ‘quantitative research design’ followed by a survey approach to collect data from Pakistan’s healthcare sector employees. 420 questionnaires were disbursed among employees, of which 350 were received back, and 332 questionnaires were finalized after data cleaning and screening. Smart-Pls was used to analyze data and assess the association among different variables. Different tests were performed including the descriptive summary, validity (convergent and discriminant), model fitness and path analysis. Results indicated that WOC significantly impacts CWB. RPCB also significantly influences the CWB. TPCB insignificantly effects CWB and WOC significantly influences RPCB and TPCB. Mediation of TPS has been insignificant, whereas the mediation of RPS has resulted as significant. The present research holds considerable theoretical and practical importance as it provides practical insights to the managerial bodies of the healthcare sector in Pakistan to make strategies for vanishing such counterproductive work behaviors of employees that damage the morale and mental peace of other workers. The limitations of this research have also been addressed in the last section.